CMOS : - Baker, R. Jacob (John Wiley &​ Sons, Incorporated, 2019)
CMOS Circuit Design, Layout, and Simulation continues to cover the practical design of both analog and digital integrated circuits, offering a vital, contemporary view of a wide range of analog/​digital circuit blocks including: phase-locked-loops, delta-sigma sensing circuits, voltage/​current references, op-amps, the design of data converters, and much more. Regardless of one's integrated circuit (IC) design skill level, this book allows readers to experience both the theory behind, and the hands-on implementation of, complementary metal oxide semiconductor (CMOS) IC desig.